Recursive Utility, Endogenous Growth, and the Welfare Cost of Volatility - Pommeret, Aude (IMF Working Papers; Working Paper ;, 2001)
This paper proposes a measure of the welfare cost of volatitliy derived from an endogenous growth model (AK) under uncertainty extended to the case of a recursive utility function which disentangles risk aversion from intertemporal elasticity of substitution. It encompasses a direct welfare cost of fluctuations and a welfare cost due to the endogeneity of the consumption. The total welfare cost of volatility increases with both the risk aversion and the intertemporal elasticity of substitution. For plausible values of the agent's preference parameters, the cost of volatility may be greater than measures bases on an exogenous process for consumption.